The Impact of Napoleon Bonaparte’s Expedition on Islamic Education in Egypt - Saminu, Muhammad; Ringgit, Awang; Rambe, Anggi Afrina (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2023)
The history of Islam records periods of advancement, decline, and reform, including in Egypt. This study examines the impact of Napoleon Bonaparte’s expedition on Islamic education in Egypt, which, although primarily a military campaign, also created opportunities for intellectual and educational reform. The research employs a qualitative method with a content analysis approach, analyzing historical documents, literature, and scholarly publications to explore the social, political, and educational influences of the expedition. The findings indicate that the presence of Napoleon and his entourage, including scholars, generated new awareness among Egyptian intellectuals, fostering the adoption of scientific methods and educational renewal. These results suggest that interactions between European colonial forces and local society can indirectly facilitate the transformation of education and the development of intellectual life in Egypt.